Plasma Exchange in Critically Ill Children: A Single-center Experience - Halil Keskin; Muhammet Şükrü Paksu; Nazik Yener; Özlem Temel Köksoy; İbrahim Kartal; Canan Albayrak; Davut Albayrak (Galenos Yayinevi, 2018)
Introduction: The aim of this study was to identify demographic and clinical characteristics of patients who were subjected to plasma exchange (PE) at our unit, and to investigate the effect of these factors on treatment outcome and patient prognosis. Methods: Demographic, clinical and laboratory data of patients who were subjected to PE between January 2012 and August 2015 were obtained from the hospital information system, medical records and the records of apheresis unit. Results: Plasma exchange was performed in 40 patients for 168 times throughout the study. The median age of the patients was 9.4 (range: 1.5-17.3) years, with a male/female ratio of 1.35. Of the patients, 47.5% had an underlying disease. The most common comorbidity was malignancy. The most common indication for PE was sepsis-related multiple organ failure (n=19, 47.5%). The mortality rate was higher in patients with an underlying chronic disease, compared to those without (25% and 7.5%, respectively). No life-threatening complication associated with the apheresis procedure was observed. Conclusion: Our results suggest that PE can be safely performed in children. It seems that indication for PE and the presence of underlying diseases are affecting the mortality rate.